Coupled vibration characteristics of a drive system during automatic transmission power shifting - Chengyun Su; Meitao Wang; Yanling Yuan; Wenguan Li; Xiao Liu (Measurement + Control, 2025)
To elucidate the vibration principle and effectively mitigate noise during power shifting in an automatic transmission, this study investigates a power split automatic transmission. The transmission principle and power flow path are analyzed using the centralized mass method and Lagrange equation. A vibration model that encompasses both clutches and gears is established for the coupling system. The dynamic model and vibration principle of clutches during power shifting are determined. Subsequently, the dynamic vibration characteristics are solved considering engine speed as a time-domain excitation source, while analyzing the dynamic transmission error. By optimizing gear modification parameters and structural stiffness, measures to reduce both dynamic transmission error and vibrational response during power shifting are obtained. Through vehicle-based vibration analysis and testing, a comparison is made between optimized gear parameters’ vibrational response characteristics and noise test data; revealing significant improvement in vibration performance by 3%–6%. A new approach is suggested for studying the vibration characteristics and dynamic response of automatic transmissions during power shifting, which provides both theoretical importance and practical benefit in effectively minimizing vehicle vibrations and noise.